IDENTIFIKASI POPULASI DAN KUALITAS SUSU SAPI PERAH PADA ANGGOTA KUBE PSP MAJU MAPAN DESA KEMIRI KECAMATAN JABUNG KABUPATEN MALANG - Khusnul Khotimah (Jurnal Gamma, 2011)
Khusnul KhotimahStaf Pengajar Jurusan Produksi Ternak , Fakultas , Universitas Muhammadiyah MalangAlamat Korespondensi : Jln. Terusan Siguragura c/4 MalangEmail: thuthul17@yahoo.comABSTRACTThe purpose of this study were: (1). to know the number of population and non-lactating dairycattle lactation on each member of the KUBE PSP Equipments at kemiri Village Kecamtan JabungMalang Regency. (2). to be able to determine the population of a balanced comparison betweenlactating and non lactating cows are maintained ranchers people KUBE members Equipments PSPPecan Village District Jabung Malang Regency. (3). To know the quantity and quality of milk producedby dairy farm Equipments PSP KUBE members Pecan Village District Jabung Malang.Based on the number of lactating cattle population (pregnant or lactating tiadak) perekor averagedaily milk production for each region is a Tengo 6:55 liter, 7.8 liter kemiri village, and karanglo,lemabang and kresik at 6:04 liter. Whereas if it is based on the number of farmers are paid anaverage milk production of farmers from the tengo village at 10:28 liter; from 11:03 liter village, andkaranglo lemabang, kresik rate of 11 liters.The conclusion of this study is the population of dairy cows PSP Equipments KUBE membersoverall, with 125 active members when the study of 366 dairy cows with details of 201 lactatingcows (58 lactating pregnant and 143 lactating not pregnant), cows not as many as 23 head 17pregnant animals, pedt (23 males and 34 females), 75 dry cows. Volume of milk produced bylactating cows sebaesar 1340.5 201 liters per day or an average per day per head 6.7 liter, with 28%of the cattle population in a state of lactation milk quality average production of the IPS is intended,by at least 2.7% prpotein , Fat 3.7-4%, and 11.5-12.2 TS productivity (milk volume) is still low due,the lactation factor above 10 months old, renewal (replacement) above 5 times the lactation, and